Behavior of Rice Farmers in the Use of Personal Protective Equipment During Compounding and Spraying Pesticides in Meunasah Tuha Village, Sukamakmur District, Aceh Besar Regency in 2024 - Nasrulah, Nasrullah; Junaidi, Junaidi; Kartini, Kartini; Syahrizal, Syahrizal (Aceh Sanitation Journal, 2025)
Unsafe use of pesticides without personal protective equipment (PPE) can cause negative impacts on farmers' health, including the risk of acute and chronic poisoning. Meunasah Tuha Village, Sukamakmur District, Aceh Besar Regency is one of the agricultural areas where the use of pesticides by rice farmers still does not fully meet occupational safety standards. This study aims to determine the behavior of rice farmers in the use of personal protective equipment during compounding and spraying pesticides, reviewed from the aspects of knowledge, attitudes, and actions. This study is a quantitative descriptive study with a total sampling technique on the entire population consisting of 30 rice farmers. Data was collected through a questionnaire that measured farmers' knowledge, attitudes, and actions towards the use of PPE. The research was carried out from January to February 2024 in Meunasah Tuha Village. The results of the study showed that 60% of farmers had good knowledge, 80% showed good attitudes, but only 40% showed good actions in the use of PPE. In addition, only 40% of farmers use PPE when mixing and spraying pesticides, while the other 60% do not use PPE completely. The conclusion shows that although farmers' knowledge and attitudes towards the use of PPE are relatively good, real actions in the field are still low. This shows the need for further education and supervision of the practice of safe use of pesticides among farmers.